Languages used in the Vilniškiai subdialect - Kardelis, Vytautas (Lietuvių kalba, 2013)
Based on the data collected during dialectological expeditions in 2009–2012 in the districts of Švenčionys, Ignalina and Utena, the article discusses the state of the languages used in the area under investigation. Since the expeditions were more of a pilot study type of research, the data provided in the article are preliminary and are indicative of possible guidelines for a further, comprehensive and thorough investigation. With respect to the languages used, the whole region under investigation could be divided into the following areas: Linguistically homogeneous or more or less homogeneous areas: the area of dialectal language, marked by the usage of either the subdialect of Vilniškiai or Uteniškiai (the area of Labanoras–Ignalina–Salakas); the areas of the variations of Slavic languages in which: a) Slavic language variations are dominant with minimal use of Lithuanian (area of Gaidė), b) there is some linguistic dynamics and change in linguistic attitudes (area of Bačkininkai). Linguistically heterogeneous areas: Slavic language variations are used together with partially non-dialectal Lithuanian, however, Slavic language variations dominate. These areas include the regions of Pabradė-Joniškis and Turmantas; the dialect is used together with Slavic language variations, but the Lithuanian language is dominant (the dialect and partially non-dialectal language). This area encompasses Strūnaitis-Švenčionėliai, Didžiasalis, Neverėnai; the dialect, Slavic language variations and non-dialectal Lithuanian are used (Svirkos-Adutiškis area). This division could be useful for prospective sociolinguists and especially valuable in the research of language contacts; in addition, it may facilitate researchers in their choice of methodology for studies of this kind.